1974
DOI: 10.1139/v74-294
|View full text |Cite
|
Sign up to set email alerts
|

The Aldol Condensation of Acetaldehyde: the Equilibrium Constant for the Reaction and the Rate Constant for the Hydroxide Catalyzed RetroAldol Reaction

Abstract: An indirect thermochemical estimate of the equilibrium constant for the aldol condensation of acetaldehyde suggested that this reaction was much less irreversible than has been believed. The rate of the hydroxide catalyzed retroaldol reaction has been measured; k21 = 2.8 × 10−3 M−1 s−1 at 25°, so that the equilibrium constant is 4.0 × 102 M−1. The γ value for acetaldehyde as addend is 0.40. The enthalpy change for the aldol reaction is −9.84 kcal/mol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 7 publications
2
23
0
Order By: Relevance
“…2. We had previously (2) found that for crotonaldehyde, 2 b , k,, , kz3, and l / K l showed a dependence upon hydroxide concentration of the form: Similar behavior appears to be shown here, although one cannot be very confident because the variation with changing hydroxide concentration is only clearly greater than experimental error for k z I . Table 2 shows the second order rate constants for the individual steps evaluated in this work, corrected where appropriate to zero hydroxide ion concentration.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…2. We had previously (2) found that for crotonaldehyde, 2 b , k,, , kz3, and l / K l showed a dependence upon hydroxide concentration of the form: Similar behavior appears to be shown here, although one cannot be very confident because the variation with changing hydroxide concentration is only clearly greater than experimental error for k z I . Table 2 shows the second order rate constants for the individual steps evaluated in this work, corrected where appropriate to zero hydroxide ion concentration.…”
supporting
confidence: 84%
“…Thus one can see no sign of the two stages which are believed to be essential for this reaction (eqs. [I] and [2])…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction turned out to be somewhat more difficult to sort out, but we have now completed the kinetic analysis, and wish to report it in turn. This provides another example of a fully analyzed aldol condensation, to add to those we (1,(4)(5)(6)(7)(8)(9)(10) and others (1 1-14) have previously reported. To complete the analysis we had to develop computer programs allowing us to fit simultaneously multiple sets of data described by equations with common parameters.…”
Section: Introductionsupporting
confidence: 64%
“…In the C2 pathway, the C−C bond remains intact and ethanol can be oxidized to acetaldehyde and acetic acid. In an alkaline medium, acetate is stable and acetaldehyde undergoes polymerization [10,11]. This can be compared with the C1 pathway, in which C−C bond cleavage takes place, producing adsorbed CO and adsorbed CH x , which subsequently oxidize to CO 2 which remains in solution as carbonate in alkaline media.…”
Section: Introductionmentioning
confidence: 99%